EFEKTIVITAS MODEL PEMBELAJARAN INQUIRY DENGAN METODE JIGSAW TERHADAP HASIL BELAJAR ASSESMENT PEMBELAJARAN MATEMATIKA - Stefania Baptis Seto; Maria Fatima Mei; Gregorius Taga (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2021)
The purpose of this study is to find out the influence of the use of inquiry learning models with jigsaw methods on the learning outcomes of mathematics learning assessment subjects of mathematics education study programs of the University of Flores. The research methods used in this research are quantitative with quasi experiment design. The population in this study were all students of the 6th semester of the University of Flores mathematics education study program that programed the mathematics learning assessment course. The sample in the study was 72 students divided into two classes including a 20-student experimental class) and a control class (16 students). The test instrument used in this study is a description test of 5 questions. The results of the study obtained that the value of 0.000 < 0.05 so that there was a significant difference with a probability of 0.05 in the results of the assessment of mathematics learning courses between students in experimental classes and students in control classes. Mathematics learning assessment courses are guided by guided inquiry learning models combined with jigsaw methods empirically proven to improve student learning outcomes in mathematics learning assessment courses.